SISTEM INFORMASI INVENTARIS BARANG BERBASIS JAVA PADA UMMY SOLOK - Yulhan Yulhan; Novia Lestari (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2020)
The use of information technology implemented through information systems makes it easy for users to carry out work, not only in terms of managing data but also when evaluating data to make it easier to produce reports according to user needs. Inventory data is an important element in a company/agency that must be managed properly, which requires accuracy and a relatively long time allocation, so that all items can be recorded perfectly. Therefore, by utilizing information technology, one of which is an information system designed with the Java programming language, data recording can be carried out more neatly and effectively because it is managed in the form of a database, so that the resulting information can be faster, more precise and relevant. This inventory information system is designed to simplify the process of recording data items which are quite a lot and complicated and are still managed manually at UMMY Solok. The result of the implementation of this inventory information system is that it is easier to record inventory data and make inventory reports. With this inventory information system, the work of inventory data at UMMY Solok is expected to be done more quickly and produce more accurate reports of inventory data at UMMY Solok.